2020
DOI: 10.3389/fnins.2020.00584
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Accuracy for Multiclass Mental Workload Detection Using Long Short-Term Memory for Brain–Computer Interface

Abstract: Cognitive workload is one of the widely invoked human factors in the areas of humanmachine interaction (HMI) and neuroergonomics. The precise assessment of cognitive and mental workload (MWL) is vital and requires accurate neuroimaging to monitor and evaluate the cognitive states of the brain. In this study, we have decoded four classes of MWL using long short-term memory (LSTM) with 89.31% average accuracy for brain-computer interface (BCI). The brain activity signals are acquired using functional near-infrar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 82 publications
(135 reference statements)
1
41
0
1
Order By: Relevance
“…First, the proposed deep learning approach is based on CNNs, but there are other promising neural network models-such as long short-term memory (LSTM)-which are known to be particularly effective for dealing with time-series data. Asgher et al (2020) reported that the deep learning framework based on LSTM outperformed conventional machine learning and CNNbased algorithms in the assessment of cognitive and mental workload using fNIRS. Therefore, it would be worthwhile to compare the performance of various deep learning approaches in the implementation of subject-independent fNIRS-based BCI.…”
Section: Discussionmentioning
confidence: 99%
“…First, the proposed deep learning approach is based on CNNs, but there are other promising neural network models-such as long short-term memory (LSTM)-which are known to be particularly effective for dealing with time-series data. Asgher et al (2020) reported that the deep learning framework based on LSTM outperformed conventional machine learning and CNNbased algorithms in the assessment of cognitive and mental workload using fNIRS. Therefore, it would be worthwhile to compare the performance of various deep learning approaches in the implementation of subject-independent fNIRS-based BCI.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, deep learning techniques, such as convolution neural network (CNN) and recurrent neural network (RNN) have been utilized for automatic feature extraction, pre-processing, and classification (Zhang et al, 2017;Yang et al, 2018;Tayeb et al, 2019). The obtained results have been promising when compared to the conventional classifiers (Trakoolwilaiwan et al, 2017;Chiarelli et al, 2018;Kumar et al, 2019;Asgher et al, 2020;Ghonchi et al, 2020). Considering the improvement in accuracy obtained using deep learning techniques, even in light of the limited amount of data and fewer pre-processing requirements, this improvement motivates us to work upon the combination of such techniques with MSVD in the future.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with the pioneer study [ 45 ], which could achieve 100% by conducting the task with a 20 s time window. With the development of deep learning, an improved classification may be achieved by utilizing the hybrid modality (i.e., EEG and fNIRS) [ 49 , 50 ] advanced machine learning algorithms, such as long-short team memory [ 51 ] and deep neural network [ 52 ]. In addition, in this study, we applied red squares with the text indicators to guide the participants to select the corresponding control commands.…”
Section: Discussionmentioning
confidence: 99%